Colonization and domestic service
1 online resource (xvi, 365 pages)
Keywords: "This groundbreaking book brings together two key themes that have not been addressed together previously in any sustained way: domestic service and colonization. Colonization offers a rich and exciting new paradigm for analyzing the phenomenon of domestic labor by non-family workers, paid and otherwise. Colonization is used here in its broadest sense, to refer to the expropriation and exploitation of land and resources by one group over another, and encompassing imperial/extraction and settler modes of colonization, internal colonization, and present-day neo-colonialism. Contributors from diverse fields and disciplines share new and stimulating insights on the various connections between domestic employment and the processes of colonization, both past and present, in a range of original essays dealing with Indonesian, Canadian Aboriginal, Australian Aboriginal, Pacific Islander, African, Jamaican, Indian, Chinese, Anglo-Indian, Sri Lankan, and "white" domestic servants"--